Study of Coupling Values and Case Library: An Example of Civics in Finance Courses - Zhang, Bo; Dong, Jie (International Journal of Social Sciences and Public Administration, 2024)
In the modern education system, ideological and political education plays a crucial role, especially in the cultivation of students’ comprehensive quality plays a fundamental role. As a discipline that emphasizes both theory and practice, the content of finance not only involves the teaching of professional knowledge, but also contains rich ideological and political education resources. This paper focuses on the construction and application of the case library in the finance curriculum and explores its important role in ideological and political education. Through in-depth discussion of the application of the case library in the ideological and political education of the finance curriculum, we analyze how it influences and promotes the formation of students’ values, aiming to put forward a set of systematic strategies to realize the deep integration of the case library and values education.